GUIDELINES FOR DEVELOPING INFORMATION SECURITY TRAINING AND AWARENESS PROGRAMS IN GOVERNMENT AGENCY: THE PERSPECTIVE OF ADDIE INSTRUCTIONAL DESIGN MODELS (A CASE STUDY IN INDONESIAN GOVERNMENT AGENCY) - Ma’ruf, Kholif Faiz; Rochman, Muhammad Machbub (PEOPLE: International Journal of Social Sciences, 2019)
Ideally, every government agency must be able to develop training programs and information security awareness in its own environment. But the fact is in Indonesia, not all of government agencies have implemented training programs and information security awareness. Thirteen percent of the respondents surveyed said they already had the program but were not structured and had no guidance, so the program was not well organized. This study provides a structured guide to building an effective information security training and awareness program, based on the ADDIE instructional design model approach (analyze, design, develop, implement, and evaluate). The results of the study state that the ADDIE instructional design model can be used to construct training programs and information security awareness in government agencies in a structured manner and can guarantee that training, awareness, education and professional development are not stagnant and can always be relevant in answering information security issues that occur in organizations.